Analisis Deiksis Pada Cerpen “Dilarang Menyanyi Di Kamar Mandi” Karya Seno Gumira Ajidarma - Dea Puspita Sari (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This research aims to describe the use of deixis in literary works, especially short stories. The use of deixis is quite important in the process of interaction and communication, including in short stories which are quite dense in writing because they are related to indicating something and leading to certain references or points of reference and are bound by the context of the utterance. The data for this research is in the form of deixis data originating from the short story